“Determinación de rangos de la pmsg (gonadotropina sérica de yeguas preñadas) para utilizarla como prueba complementaria en yeguas gestantes” - Bayas Vizcaíno, Karen de los Ángeles (2023)
The objective of this research work is focused on the "Determination of PMSG (serum gonadotropin of pregnant mares) ranges to be used as a complementary test in pregnant mares",statistical methodologies were used to determine variations in different stages of gestation in French, Dutch, Quarter Horse, English, PRA (Purebred Arabian Breed), PRE (Pure Spanish Breed), Lusitano, mestizo and adult Creole breeds, and 23 mares were handled, the purpose is to determine the PMSG ranges for gestation diagnosis, it was performed in groups of four mares served, with a range of five days difference: 0; 15 to 20; 35 to 40; 60 to 65; 80 to 85 and from 110 to 115 days of pregnancy, which were subjected to blood extraction by venipuncture and perform the Elisa test to confirm if this will be useful as a complementary hormonal test, through the Elisa method the PMSG concentrations were measured in the mentioned days with the objective of determining the hormonal levels and how is the dynamics of PMSG. For the analysis of the results, the hormone concentrations in the pregnant mares are (p